Cervical Supine Side-Bending versus Cervical Supine Traction Radiographs: Which Is Better in Predicting Proximal Thoracic Flexibility for Lenke 1 and 2 Adolescent Idiopathic Scoliosis? - Chiu, Chee Kidd; Bashir, Elrofai Suliman; Chan, Chris Yin Wei; Kwan, Mun Keong (Korean Society of Spine Surgery, 2018)
Study Design: Prospective cohort study. Purpose: This study compared cervical supine side-bending (CSSB) and cervical supine traction (CST) radiographs to assess the flexibility and predict the correctability of the proximal thoracic (PT) curve for patients with adolescent idiopathic scoliosis (AIS) classified as Lenke 1 and 2. Overview of Literature: Knowledge of the flexibility of the PT curve is crucial in the management of patients with AIS. There are no reports comparing CSSB and CST radiographs to assess this parameter. Methods: Thirty patients with Lenke 1 and 2 AIS scheduled for posterior spinal fusion surgery were recruited. A standing whole spine radiography and physician-supervised CSSB and CST radiographies were performed. Patient demographic and radiological parameters were recorded, including age, gender, weight, height, body mass index, PT angle, main thoracic angle, CSSB PT angle, CST PT angle, and postoperative PT angle. From the data collected, the curve flexibility and curve correction index were calculated and compared. Results: CSSB had a significantly (p < 0.05) smaller PT angle (16.6°±10.4°) in comparison to CST (23.7°±10.7°). CSSB had significantly (p < 0.05) greater flexibility (44.2%±19.7%) in comparison to CST (19.5%±18.1%). The CSSB correction index (1.2±0.9) was significantly closer to 1 in comparison to the CST correction index (4.4±5.3). There was no difference (p =0.72) between the CSSB PT angle (16.6°±10.4°) and the postoperative PT angle (16.1°±7.5°). However, the CST PT angle (23.7°±10.7°) was significantly (p < 0.05) larger than the postoperative PT angle (16.1°±7.5°). Conclusions: CSSB radiographs were better for demonstrating PT flexibility and more accurately predicted correctability in comparison to the CST radiographs.